Strategic Management of Teacher Professionalism Development through the Teaching Factory Model - Andriani, Tuti Andriani; Faruq, Umar; Dinata, Yuriyan (JURNAL AL-TANZIM, 2026)
This study examines strategic management in developing teacher professionalism through the Teaching Factory (TeFa) approach. The Research aims to analyse strategic management processes, identify supporting and inhibiting factors, and examine the contribution of TeFa-based professional development to learning quality and student work readiness. A qualitative approach was employed using in-depth interviews, non-participant observations, and document analysis. Data were analysed through data reduction, data display, and conclusion drawing. The findings indicate that TeFa-based teacher professional development is managed through systematic stages of strategy formulation aligned with institutional vision, strategy implementation through delegated managerial roles and annual planning, and strategy evaluation of implemented programs. Supporting factors include institutional readiness and collaboration with industry partners, while inhibiting factors involve limited infrastructure, budget constraints, and unequal industry absorption capacity. The study also reveals that TeFa-based professional development contributes to improved instructional quality and enhanced student readiness for the world of work. These findings highlight the importance of strategic management in optimising the implementation of the Teaching Factory as a sustainable model for teacher professionalism development.